2008
DOI: 10.1016/j.febslet.2008.10.046
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for screening an inhibitor of viral silencing suppressors, which attenuates symptom development of plant viruses

Abstract: To find out whether we can control plant virus diseases by blocking viral RNA silencing suppressors (RSSs), we developed a strategy to screen inhibitors that block the association of RSSs with siRNAs using a surface plasmon resonance assay. The screened chemicals were tested in competition with RSSs for binding to siRNAs using a mobility shift assay. We then confirmed that tested chemicals actually inhibited the RSS activity in vivo using a protoplast assay which was developed for this purpose. This entire sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Because rgs-CaM was reported to interact with TEV HC-Pro (13), we tested for in vitro proteinprotein interactions between purified rgs-CaM and RSS proteins using surface plasmon resonance (SPR) analysis (14). We found that rgs-CaM interacted with the HC-Pro protein encoded by the potyvirus, turnip mosaic virus (TuMV) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because rgs-CaM was reported to interact with TEV HC-Pro (13), we tested for in vitro proteinprotein interactions between purified rgs-CaM and RSS proteins using surface plasmon resonance (SPR) analysis (14). We found that rgs-CaM interacted with the HC-Pro protein encoded by the potyvirus, turnip mosaic virus (TuMV) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The siRNA-binding activity of RSSs is important for their antisilencing activities (14,19,32). Therefore, by interfering with siRNA binding, rgs-CaM might attenuate RSS antisilencing activity.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that CAT3 may inactivate the RSS activity of 2b by binding with 2b, thus inhibiting CMV multiplication. To investigate the effect of CAT3 on the RSS activity of 2b, we used a protoplast assay that we have previously developed to measure viral RSS activities on the cellular level (Shimura et al, 2008). As shown in Figure 9B, CAT3 expression actually decreased the RSS activity of 2b by 30% to 40%, but it did not affect another virus RSS, P19.…”
Section: Cat3 Expression Compromises Cell Death Induced By 2b In Protmentioning
confidence: 99%
“…Protoplasts were prepared from leaves of N. benthamiana and used to analyze RSS activity essentially as described by Shimura et al (2008). For this assay, we used the Dual-Luciferase Reporter Assay System (Promega) using firefly luciferase (Fluc) and Renilla luciferase (Rluc).…”
Section: Protoplast Assay For Rss Activitymentioning
confidence: 99%
“…Kinetic parameters of the binding in vitro of the 2b protein and eight mutant variants to three types of sRNAs and a viral RNA The ability of the CMV 2b protein to bind to sRNAs in vitro had been demonstrated previously (Goto et al 2007;Rashid et al 2008;Shimura et al 2008), and the affinity of an Escherichia coli-expressed 2b protein tagged with maltose-binding protein (MBP-2b) for a 39 biotinylated siRNA in vitro was also determined (Shimura et al 2008). Furthermore, using a battery of six 2b protein mutants a correlation between ability to bind to siRNAs in vitro and suppressor activity had been found (González et al 2010).…”
Section: In Vivo Characterization Of 2b Protein Mutantsmentioning
confidence: 99%